2016
DOI: 10.1007/s12291-016-0623-4
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of α-Tocopherol Attenuates Minerals Disturbance, Oxidative Stress and Apoptosis Occurring in Favism

Abstract: The favism is a metabolic disease that characterized with an acute hemolytic anemia where α-tocopherol is a type of tocopherol accumulated inside the human body. The objective of such a study was established to evaluate the effect of α-tocopherol in favism disorders. A total of 75 human cases were divided into 5 groups as follow; group 1 normal cases without any treatment and group 2 normal cases orally administrated α-tocopherol (200 mg/kg) once a day over 30 days period. Group 3 favism patients without any t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…These results were due to the higher levels of free radicals' production which did not only react with erythrocytes but also with other membranes and tissues to cause tissues damages and loss of functional properties of many tissues (Marquardt et al , 1997). These results were in accordance with previous studies (Koriem et al , 2008, 2016, 2017 and Koriem and Arbid, 2018). On the other hand, the oral administration with pickled olives+ V. faba in favism animals' models, pickled olives + vicine-treated animals and pickled olives + convicine-treated animals returned all the above mentioned parameters to the control levels.…”
Section: Discussionsupporting
confidence: 94%
“…These results were due to the higher levels of free radicals' production which did not only react with erythrocytes but also with other membranes and tissues to cause tissues damages and loss of functional properties of many tissues (Marquardt et al , 1997). These results were in accordance with previous studies (Koriem et al , 2008, 2016, 2017 and Koriem and Arbid, 2018). On the other hand, the oral administration with pickled olives+ V. faba in favism animals' models, pickled olives + vicine-treated animals and pickled olives + convicine-treated animals returned all the above mentioned parameters to the control levels.…”
Section: Discussionsupporting
confidence: 94%
“…The increase in lipid peroxidation of mitochondria may result in the disintegration of the mitochondrial membrane ultrastructure, which in turn can affect the membrane-bound LDH function resulting in LDH inhibition. These results are in agreement with that of Koriem et al (2008Koriem et al ( , 2015Koriem et al ( , 2016Koriem et al ( , 2017Koriem et al ( , 2018. The effect of vitamin E might be through the scavenging of reactive oxygen species induced by V and C (Diemer et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…All the injections were stayed for 1 month period. The one-month period was depended on previous studies Arbid, 2018, 2020;Koriem et al, 2008Koriem et al, , 2016Koriem et al, , 2017.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our results, Koriem et al [49] a study published in 2017, showed that G6PD deficiency patients with favism who take VitE for one month had a high level of hemoglobin, hematocrit, and serum G6PD, which was dose-dependent, increasing the dose of VitE was associated with better outcomes. We cannot include this study in our analysis as it reported the results without reporting the baseline values, so we cannot calculate the mean change.…”
Section: Agreement and Disagreement With Previous Studiessupporting
confidence: 93%